Experimental assessment of a thermoelectric subcooler included in a transcritical CO2 refrigeration plant. (25th May 2021) - Aranguren, P.; Sánchez, D.; Casi, A.; Cabello, R.; Astrain, D.
Highlights: A CO2 refrigeration system including thermoelectric subcooling is analysed. Experimental tests are performed at −10 °C and ambient conditions of 30 °C/RH 55%. Voltage supply to thermoelectric modules and heat exchangers' fans are  modified. At optimum conditions thermoelectric subcooling increases COP up to 11.3%. At optimum conditions thermoelectric subcooling increases capacity up to 15.3%. Abstract: This study brings an experimental research that has tested a real transcritical CO2 vapor compression cycle that includes a thermoelectric subcooler at the exit of the gas-cooler of the refrigeration plant. The aforementioned technology hybridization increases the COP of refrigeration systems as long as the subcooling system is properly designed and operated. The experimental facility studied has been tested under constant ambient conditions (30 °C and relative humidity of 55%) and maintaining the evaporating temperature at −10 °C; while the voltage supplied to the thermoelectric modules and the thermal resistances of the heat exchangers located at the thermoelectric subcooler have been experimentally modified. The voltage supplied to the fans located at these heat exchangers was modified implying thermal performance deviation of the heat exchangers and a variation on the power consumption of the cooling facility. The results show an experimental increase on the COP of 11.3% while the cooling capacity increases a 15.3% when the thermoelectric modules are supplied with 2 V and the fans with 9 V. Moreover, the importance of optimizing the voltage supplied to the thermoelectric modules and to the auxiliary consumption of the thermoelectric subcooler is addressed along this research.